
Method:
Solve the same system of equations by the method of substitution. 2x + y = 4  Equation 1 x − y = −1  Equation 2 Solution: Take equation 1: 2x + y = 4  Equation 1 2x + y = 4 y = 4  2x Substituting y in equation 2 x − y = −1  Equation 2 x − (4 − 2x) = −1 Solving for x x − 4 + 2x = −1 3x = −1 + 4 3x = 3 x = 1 To find y, substitute x = 1 in equation 1 2x + y = 4  Equation 1 2x + y = 4 2(1) + y = 4 2 + y = 4 y = 4  2 y = 2 x = 1 and y = 2 Answer: (1,2) Directions: Solve the linear equations by the method of substitution. Also write at least 5 examples of your own. 